2007
DOI: 10.1007/s10517-007-0353-y
|View full text |Cite
|
Sign up to set email alerts
|

Some pharmacological properties of immunotropic preparation from porcine skin

Abstract: We studied pharmacological properties of immunotropic preparation from porcine skin (skin resorption effect and acute and chronic toxicity). It was demonstrated that the preparation did not damage the skin during evaluation of skin-resorption effect; evaluation of acute and chronic toxicity revealed no changes in the general state of experimental animals and histological structure of visceral organs and skin; evaluation of chronic toxicity showed that the preparation induced no changes in blood biochemical par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Preclinical study of K-activin was performed at Laboratory of Experimental Hemosorption and Oxidative Methods of Detoxification, Institute of Physicochemical Medicine. Skin-resorption effect, acute toxicity, chronic toxicity [6] and allergic effects of K-activin in the reactions of systemic anaphylaxis (anaphylactic shock) and active cutaneous anaphylaxis were evaluated. Preliminary data obtained on volunteers (psoriasis patients) showed that the preparation produced a therapeutic effect.…”
mentioning
confidence: 99%
“…Preclinical study of K-activin was performed at Laboratory of Experimental Hemosorption and Oxidative Methods of Detoxification, Institute of Physicochemical Medicine. Skin-resorption effect, acute toxicity, chronic toxicity [6] and allergic effects of K-activin in the reactions of systemic anaphylaxis (anaphylactic shock) and active cutaneous anaphylaxis were evaluated. Preliminary data obtained on volunteers (psoriasis patients) showed that the preparation produced a therapeutic effect.…”
mentioning
confidence: 99%